Diagnóstico da importância da comercialização e distribuição dos produtos artesanais derivados do leite no Alto Sertão Sergipano - Silva, Fabiana Oliveira da (2019)
The presence of artisan products derived from milk in the free trade fairs and markets is str ong due to the localpopulation's culture in consuming them, besides the region being classif ied as the dairy basin of the state of Sergipewhich holds one of the largest milk productions of the region in which the municipalities de Canindé de São Francisco, Porto da Folha, Nossa Senhora da Gloria, Nossa Senhora Lourdes were carried out, where the surveys were conducted, in which questionnaires were applied, the purpose was to evaluate whether the commercialization of Such products, Coalhocheese, precooked cheese, cream, butter, dulce de leche,milk cocada , milk bullet and yoghurt. Data were collected through semi structured questionnaires, applie d in places such as super markets, grocery stores, free trade fairs,bakeries, and at other point s considered by traders as strategic in which 45 were applied. Questionnaires, in which ca n be verified that 95.6% of the marketed products are produced in the region, 42% is marke ted in free fairs, 37.8%have the trade of these products as the only source of income. The m ost found products were rennet cheese, 22.5%, cream 19.7% and butter 16.2%. The trade in dairy products in the high sertão of Ser gipe contributes directly to the economic system and to the local development, and conseque ntly to the social reproduction of the family units of production of handcrafted milk derivatives.